Intralesional excision as a surgical strategy to manage keloid scars: what's the evidence? - Ioannis Goutos (SAGE Publishing, 2019)
Introduction: Keloid scars are a particularly challenging clinical entity and a variety of management approaches have been described in the literature including intralesional surgery. The current literature lacks a summative review to ascertain the evidence base behind this surgical approach. Methods: A comprehensive English literature database search was performed using PubMed Medline, EMBASE and Web of Science from their individual dates of inception to March 2018. We present the different rationales proposed for the use of this technique, the clinical outcomes reported in the literature as well as the scientific basis for intralesional excision of keloid scars. Discussion: A number of arguments have been proposed to support intralesional excision including avoiding injury to neighbouring non-keloidal skin and the deep layer of the dermis, removal of the most proliferative fibroblastic group as well as debulking to facilitate the administration of injectable steroid. The most current literature does not provide sufficient support for the adoption of intralesional excisions based on data emerging from basic science as well as clinical outcome studies. Conclusion: Emerging evidence supports the extralesional excision of keloid scars based on current mechanobiological, histological as well as clinical outcome data. Further trials comparing extralesional and intralesional surgical practices are eagerly awaited to ascertain the role of intralesional excisions in the keloid management arena.